2021
DOI: 10.7717/peerj.10521
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of the narrow endemicSeseli farrenyi(Apiaceae): implications for translocation

Abstract: Seseli farrenyi (Apiaceae) is an extremely narrow endemic plant, which is considered as one of the species of most conservation concern in Catalonia (NW Mediterranean Basin). Given the accelerated fragmentation and reduction of population size (of over 90%), the environmental agency of Catalonia is currently preparing a recovery plan that includes reinforcements of the extant populations. The present study is aimed at providing the necessary knowledge to carry out genetically-informed translocations, by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 58 publications
0
14
1
Order By: Relevance
“…Barret and Kohn, 1991;Ellstrand and Elam, 1993;Honnay and Jacquemyn, 2007), the results for M. catharinensis do not support the hypothesized loss of genetic diversity, which should reflect high levels of inbreeding, as a consequence of reduced population size and narrow endemism. Although contradictory to theoretical predictions, unexpectedly high levels of genetic diversity are not unusual for narrow endemics (e.g., Fernández-Mazuecos et al, 2014;Jiménez-Mejías et al, 2015;Turchetto et al, 2016;Forrest et al, 2017;Goetze et al, 2018;Sękiewicz et al, 2020;Bard et al, 2021;Garcia-Jacas et al, 2021), creating an indistinct pattern for this kind of plant species. For instance, in the studies by Fernández-Mazuecos et al (2014) and Jiménez-Mejías et al (2015), the authors highlight the paradox of genetic diversity levels in narrow and extremely narrow endemic plant species from the Mediterranean.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…Barret and Kohn, 1991;Ellstrand and Elam, 1993;Honnay and Jacquemyn, 2007), the results for M. catharinensis do not support the hypothesized loss of genetic diversity, which should reflect high levels of inbreeding, as a consequence of reduced population size and narrow endemism. Although contradictory to theoretical predictions, unexpectedly high levels of genetic diversity are not unusual for narrow endemics (e.g., Fernández-Mazuecos et al, 2014;Jiménez-Mejías et al, 2015;Turchetto et al, 2016;Forrest et al, 2017;Goetze et al, 2018;Sękiewicz et al, 2020;Bard et al, 2021;Garcia-Jacas et al, 2021), creating an indistinct pattern for this kind of plant species. For instance, in the studies by Fernández-Mazuecos et al (2014) and Jiménez-Mejías et al (2015), the authors highlight the paradox of genetic diversity levels in narrow and extremely narrow endemic plant species from the Mediterranean.…”
contrasting
confidence: 62%
“…While Fernández-Mazuecos et al (2014) found moderate levels of genetic diversity for Naufraga balearica, Jiménez-Mejías et al (2015) reported high levels of genetic diversity for Pseudomisopates rivas-martinezii. In comparison to previous genetic assessments for narrow endemics in the same regions, the authors (Fernández-Mazuecos et al, 2014;Jiménez-Mejías et al, 2015) found that, although some species have low genetic variability, most species showed moderate to high levels of genetic diversity (e.g., Sales et al, 2001;Coppi et al, 2008;Mameli et al, 2008;Mayol et al, 2012;De Castro et al, 2013;Forrest et al, 2017;Sękiewicz et al, 2020;Garcia-Jacas et al, 2021). Thus narrow endemism does not always imply limited genetic diversity.…”
mentioning
confidence: 86%
“…Five populations showed a slight loss of allelic richness or genetic diversity in the seed progeny generation compared to the adults, and three populations showed low but significant inbreeding levels in seed progeny, suggesting that the processes (genetic drift effects, crosses between relatives leading to biparental inbreeding) usually observed in fragmented populations (e.g., Aguilar et al, 2008Aguilar et al, , 2019Berjano et al, 2013;Wiberg et al, 2016) may have started. There was also evidence of recent genetic bottlenecks in LAM and WAT populations, suggesting that these populations may have incurred demographic reductions (Peery et al, 2012), as found for the self-incompatible Sesili farrenyi (Garcia-Jacas et al, 2021). No effect of flowering population size was observed on the genetic variation estimates, but the size range may be too narrow to detect any relationship.…”
Section: Genetic Status Of the Remaining Populationsmentioning
confidence: 82%
“…Several features have to be taken into account in designing the translocation. Species life-history traits, such as longevity, breeding system (e.g., selfincompatibility, dioecy, autogamy), pollen and seed dispersal abilities and clonal ability determine species sensitivity to habitat fragmentation and species response to restoration by influencing mating processes, gene flow and population genetic composition (Charlesworth, 2006;Dudash and Murren, 2008;Berjano et al, 2013;Wiberg et al, 2016;Bittebiere et al, 2020;Tierney et al, 2020;Garcia-Jacas et al, 2021). The selection of sources for translocation material (e.g., seeds, cuttings, tubers) has to be based on ecological characteristics, genetic composition and seed production and quality (Commander et al, 2018;Hoban et al, 2018;Bragg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation